1996
DOI: 10.1002/(sici)1096-9861(19960304)366:2<259::aid-cne6>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of visual callosal neurons in normal and strabismic cats

Abstract: It has been suggested that synchronous activation of cortical loci in the two cerebral hemispheres during development leads to the stabilization of juvenile callosal connections in some areas of the visual cortex. One way in which loci in opposite hemispheres can be synchronously activated is if they receive signals generated by the same stimulus viewed through different eyes. These ideas lead to the prediction that shifts in the cortical representation of the visual field caused by misalignment of the visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…It is noteworthy that strabismus is effective in enlarging callosal zone even when induced as late as postnatal day 36 (Berman and Payne, 1983). However, contradictory results were also reported by other groups, that found no changes in size of callosal zone (Bourdet et al, 1996). These discrepancies could be due to different methodological experimental procedures and different onset of pathology.…”
Section: Callosal Plasticity: How Visual Input Impacts On Interhemispmentioning
confidence: 77%
“…It is noteworthy that strabismus is effective in enlarging callosal zone even when induced as late as postnatal day 36 (Berman and Payne, 1983). However, contradictory results were also reported by other groups, that found no changes in size of callosal zone (Bourdet et al, 1996). These discrepancies could be due to different methodological experimental procedures and different onset of pathology.…”
Section: Callosal Plasticity: How Visual Input Impacts On Interhemispmentioning
confidence: 77%
“…In cat visual cortex, bilateral deprivation or enucleation result in a reduced callosal projection (44)(45)(46), whereas monocular manipulations result in expanded callosal projections (16,47,48). However, binocularity seems not to play an important organizing role in this pathway, since strabismus does not affect the pattern or number of callosal cells (49,50). Rather, the outcome of deafferentation is predicted by the effect of the manipulation on retinotopic correspondence between the two hemispheres (18,19,44,49,50).…”
Section: Discussionmentioning
confidence: 99%
“…However, binocularity seems not to play an important organizing role in this pathway, since strabismus does not affect the pattern or number of callosal cells (49,50). Rather, the outcome of deafferentation is predicted by the effect of the manipulation on retinotopic correspondence between the two hemispheres (18,19,44,49,50). In deaf animals, there may be no information available on which to base elimination of connections, as in the retention of overlapped corticocortical (51) or thalamocortical (52) arbors after visual deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…At the present time, some authors claim that strabismus leads to extended distribution of cell bodies of callosal neurons in one or both hemispheres through the stabilization of juvenile exuberant ones (Innocenti and Frost, 1979; Berman and Payne, 1983; Elberger et al, 1983). But other authors do not agree with this view (Lund et al, 1978; Bourdet et al, 1996). The same conclusion has also been proposed for callosal terminals (Lund et al, 1978; Lund and Mitchell, 1979; Berman and Payne, 1983).…”
Section: Introductionmentioning
confidence: 92%
“…Subsequent development of CC in cat visual cortex was investigated at the level of callosal terminals by combining electrophysiology and tracer injection techniques. Although controversial, some anatomical data in the literature have already suggested that procedure this may lead to asymmetric callosal connections in one hemisphere and the other in adulthood (Lund and Mitchell, 1979; Berman and Payne, 1983; but see Elberger et al, 1983; Bourdet et al, 1996). …”
Section: Introductionmentioning
confidence: 99%